Production of Giant Reedgrass for Biofuel - Robert Gilbert; Jason Ferrell; Zane Helsel (EDIS)
SS-AGR-318, a 4-page illustrated fact sheet by Robert Gilbert, Jason Ferrell, and Zane Helsel, discusses the adaptation and production of Arundo as a potential energy crop and presents measures for controlling Arundo as an escaped weed, based on initial observations in preliminary university trials and cited literature. Includes references. Published by the UF Department of Agronomy, November 2008.